Proposals for risk assessment of major cations in surface water and deep sediment: iso-cation curves, probabilities of occurrence and non-occurrence of cations - Kulahci, Fatih (Springer, 2016)
Spatial analysis and stochastic risk analysis methodologies are proposed for the characterisation of major cations (Mg, Ca, K, Na and Zn) in deep sediments and surface waters of the Keban Reservoir, Turkey. Curves denoted as iso-cation curves were drawn using the spatial analysis of the major cations. Spatial diagrams and risk assessment allowed significant conclusions about the nature of the variations in cation concentration in the reservoir. Major cations are measured at 20 different locations within the reservoir, and their comparisons are presented through both spatial distribution and risk analysis models for each ion. Their collective behaviour was also analysed by comparing spatial diagrams of surface water and deep sediment concentrations. Finally, the iso-cation curves and achievement of the occurrence and/or non-occurrence cation probabilities in any research area can be generalised to other the environment sciences. This calculation can be extended easily to cover all pollutants at micro-and macroscales.
Keywords: Risk assessment; Risk analysis; Cation; Spatial analysis; Lake